2020
DOI: 10.1186/s12889-020-08898-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of T. gondii infection with suicide: a systematic review and meta-analysis

Abstract: Background Findings on the association between Toxoplasma gondii (T. gondii) infection and suicide are contradictory. This paper aimed to resolve this uncertainty by conducting a meta-analysis. Methods We found the relevant studies using keywords include “Toxoplasmosis” and “Suicide” and the related synonyms in international databases such as ISI, Medline, and Scopus. The eligible studies were included in the meta-analysis phase. The random effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
16
1
2
Order By: Relevance
“…This suggests that T. gondii infection increases the risk of suicide with an OR of 3.77. Similar to the present study, several studies have shown that T. gondii infection represents a risk factor for suicidal behaviors ( 51 ). Associations of T. gondii seropositivity with suicide attempt, recurrent mood disorders and psychiatric patients have been documented in South Korea ( 52 ), United States ( 8 ), and Mexico ( 53 ).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that T. gondii infection increases the risk of suicide with an OR of 3.77. Similar to the present study, several studies have shown that T. gondii infection represents a risk factor for suicidal behaviors ( 51 ). Associations of T. gondii seropositivity with suicide attempt, recurrent mood disorders and psychiatric patients have been documented in South Korea ( 52 ), United States ( 8 ), and Mexico ( 53 ).…”
Section: Discussionsupporting
confidence: 90%
“…Besides that, changes in glutamate and dopamine neurotransmission have shown a key role in suicide and suicidal behavior. As a result, it was mentioned in this meta-analysis that changes in neurotransmitters can play a role in behavioral development that increases the risk of suicide [27]. In contrast to these results, we could not find any association between T. gondii seropositivity and suicidal behavior.…”
Section: Discussioncontrasting
confidence: 98%
“…A recent casecontrol study also consistent with the above observations found a higher seroprevalence among schizophrenia patients especially in suicide attempters, against the control groups, and patients with no history of suicide attempts (Akgul et al, 2021) by emotional irritation (Gohardehi et al, 2018;Sutterland et al, 2019). In addition, numerous studies demonstrated T. gondii as a replicated risk factor in human psychiatric disorders such as unknown temporal lobe epileptic seizure (Ngoungou et al, 2015;Uzorka and Arend, 2017;Sadeghi et al, 2019), Alzheimer's disease (Bayani et al, 2019), cognitive impairment in several cognitive domains including short-term verbal memory and processing speed (Gale et al, 2015;de Haan et al, 2021), depression (Kamal et al, 2020), autism (Flegr and Horacek, 2019;Nayeri et al, 2020;Al et al, 2021), suicide and suicidal behavior (Kamal et al, 2020;Soleymani et al, 2020;Postolache et al, 2021), and other neurological disorders (Desmettre, 2020;Nayeri et al, 2021). Moreover, for human hosts, latent infection may also be associated with systemic changes in human personality (Lafferty, 2006).…”
Section: The Well-established Association Of Psychiatric Disorders In...mentioning
confidence: 99%